Kajian Lingkungan Hidup Strategis Revisi Rencana Tata Ruang Wilayah (RTRW) Kota Semarang 2011-2031 untuk Pembangunan Berkelanjutan - Istandia, Ika (Jurnal Ilmiah Administrasi Publik, 2020)
The preparation of this Strategic Environmental Assessment (SEA) is mandatory for the Government and Local Governments. Based on these obligations, the SEA Semarang City Spatial Planning Revised for 2011-2031 was prepared with the aim of improving the quality of the Regional Spatial Planning which so far has not been able to solve the City's problems, such as floods and tides. This study aims to determine the process of drafting the 2011-2031 Regional Spatial Planning for the City of Semarang. The research method that will be used is descriptive qualitative method. Based on the results involving stakeholders, such as the Government, the private sector and the community (Academics and non-Government Organizations). The process of preparing the SEA does not yet reflect the maximal sustainable values (interdependency, equilibrium and justice). This is because the analysis carried out is less detailed due to data and budget limitations, so the results of the studies conducted affect the formulation of recommendations for Policies, Plans and/ or Programs (PPP).